De weg van den inwendigen vrede. - De Lehen, P.; van de Looveren, F.. (Leuven Museum Lessianum, 1930)
Study on christian (roman catholic) peace, spirituality during the interbellum (in the early 1930's)
Opgedragen aan de Koningin des Vredes
Keywords: Schoolbooks - Didactic material